With Crisis Comes Opportunity: Redesigning Performance Departments of Elite Sports Clubs for Life After a Global Pandemic - McLean, Scott; Rath, David; Lethlean, Simon; Hornsby, Matt; Gallagher, James; Anderson, Dean; Salmon, Paul M. (Frontiers in Psychology, 2021)
The suspension of major sporting competitions due to the global Covid-19 pandemic had a substantial negative impact on the sporting industry. As such, a successful and sustainable return to sport will require extensive modifications to the current operations of sporting organisations. In this article we argue that methods from the realm of Sociotechnical Systems (STS) theory are highly suited for this purpose. The aim of the study was to use such methods to develop a model of an Australian Football League (AFL) club’s football department. The intention was to identify potential modifications to the club’s operations to support a return to competition following the Covid-19 crisis. Subject Matter Experts from an AFL club participated in three online workshops to develop Work Domain Analysis and Social Organisation and Cooperation Analysis models. The results demonstrated the inherent complexity of an AFL football department via numerous interacting values, functions and processes influencing the goals of the system. Conflicts within the system were captured via the modelling and included pursing goals that may not fully reflect the state of the system, a lack of formal assessment of core values, overlapping functions and objects, and an overemphasis on specialised roles. The current analysis has highlighted potential areas for modification in the football department, and sports performance departments in general.